TECHNOLOGICAL REVOLUTION IN EDUCATION IN INDIA - Shobha, L. (International Journal of Research -GRANTHAALAYAH, 2017)
Education, normally one of the largest employers in any country, is one of the industries which have not undergone a technological revolution. We must help to move it out of the handicraft stage. With the terrible and growing shortage of qualified teachers all over the developing world, we must find ways to make good teachers more productive. This will involve investment in textbooks, in audio-visual materials and above all the use of modern communication techniques (radio, television and film) for teaching purposes.” This is remarked by Robert F. Me Namara, former President of the World Bank addressing the Board of Governors in 1968.What is the nature and scope of this Technological revolution” to be brought about in the industry of education as visualised by the world famous economist? Why has he emphasized the use of modern communication techniques for teaching purposes? In what way will this contribute to community education or solve the problems of the community? These are the questions that have to be pondered upon.